Experimental Study of Fluid Flow Losses at Several Turning Angles - Daud Orba Topayung; Paul M. Rumagit; Toban Tiku Pairunan; Tammy T.V. Pangow; Adolf Tonny Rasuh (Frontier Advances in Applied Science and Engineering, 2024)
This research, entitled Experimental Study of Fluid Flow Losses at Turns 30°, 45°, 60° and 90°, is a review of fluid (water) flow in closed channels. Fluid (water) flow in opened and closed channels is influenced by the condition of the container in which the fluid flows. One form of this influence is the occurrence of a condition which is generally known as flow loss. This condition is certainly undesirable because it will cause problems, technically the manifestation is a decrease in pressure including the speed of fluid flow. To find out the real conditions of flow losses, it is necessary to carry out research stages. The research stages were carried out in the form of system design, measurement, testing and data analysis. The system is designed with a pump device, where the fluid is pumped from a holding container, then flows into the installation area or closed channel which is made using ½" PVC pipe and is equipped with a Pressure Gauge measuring instrument to measure pressure and a Flow meter to measure flow discharge, placing bends. with angles of 30, 45, 60 and 90 degrees. Indication of loss is indicated by a decrease in pressure measured at the pressure gate, while indication of a decrease in flow velocity is calculated using an equation with the flow input variable measured from the flow meter.